Permissive hypercapnia for severe acute respiratory distress syndrome in immunocompromised children: A single center experience. - Hans Fuchs; Nicola Rossmann; Manuel B Schmid; Manfred Hoenig; Ulrich Thome; Benjamin Mayer; Daniel Klotz; Helmut D Hummler (PLoS ONE)
Background Controlled hypoventilation while accepting hypercapnia has been advocated to reduce ventilator-induced lung injury. The aim of the study was to analyze outcomes of a cohort of immunocompromised children with acute respiratory distress syndrome (ARDS) ventilated with a strategy of stepwise increasing PCO2 targets up to 140 mm Hg. Methods Retrospective analysis of outcomes of a cohort of children with oncologic disease or after stem cell transplantation and severe respiratory failure in comparison with a historical control cohort. Results Out of 150 episodes of admission to the PICU 88 children underwent invasive mechanical ventilation for >24h (overall survival 75%). In a subgroup of 38 children with high ventilator requirements the PCO2 target ranges were increased stepwise. Fifteen children survived and were discharged from the PICU. Severe pulmonary hypertension was seen in two patients and no case of cerebral edema was observed. Long term outcome was available in 15 patients and 10 of these patients survived without adverse neurological sequelae. With introduction of this strategy survival of immunocompromised children undergoing mechanical ventilation for >24h increased to 48% compared to 32% prior to introduction (historical cohort). Conclusions A ventilation strategy incorporating very high carbon dioxide levels to allow for low tidal volumes and limited inspiratory pressures is feasible in children. Even severe hypercapnia may be well tolerated. No severe side effects associated with hypercapnia were observed. This strategy could potentially increase survival in immunocompromised children with severe ARDS.